Testosterone Levels And Dna Fragmentation Index In Male Undergoing Intrauterine Insemination After Vitamin D3 Supplementation - Wijayanti, Agung Sari; Budihastuti, Uki Retno; Melinawati, Eriana; Laqif, Abdurahman; Fahsan, Fatmiyanti (Indonesian Basic and Experimental Health Sciences, 2024)
Nutrition is one of the factors that contribute to male infertility. Vitamin D3 are known to affect spermatozoa and usually served in fertility supplementation in doses of 400 and 1000 IU. Low levels of vitamin D3 have been linked to decreased sperm quality and quantity. This research would like to know the effect of Vitamin D3 to the DNA Fragmentation Index (DFI) and Testosterone blood level in men undergoing intrauterine insemination (IUI). This was an analytical observational study with two groups and a pretest-posttest design. Seventeen men aged 20 to 45 who were undergoing the IUI program and did not have diabetes or hypertension are participate in this study. Sperm DFI was determined by using an ELISA method with a DNA Kit. Blood testosterone levels in ng/mL units was measure using ELISA. IBM-SPSS version 22 was used to perform univariate and bivariate analysis on the collected data. The blood level of Vitamin D3 was significantly increased after the intervention of six week Vitamin D3. Meanwhile, this study shows there are no differences in the level of blood testosterone before and after treatment. The DFI was significantly increased in the 400 IU groups.